1995
DOI: 10.1111/j.1476-5381.1995.tb16349.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E deficiency on vasomotor activity and ultrastructural organisation of rat thoracic aorta

Abstract: 1 The effects of vitamin E deficiency were evaluated in aortic rings isolated from rats maintained on a diet deficient in vitamin E. 2 Endothelium-dependent vasodilator responses to acetylcholine (ACh) and calcium ionophore, A23187, were reduced in preparations from treated animals, compared to the age-matched controls. The maximal vasodilatation to ACh was 66.4 ± 9 (n = 4) and 38.8 ± 7 (n = 4) % in control and 10 monthtreated preparations, respectively. 3 The endothelium-independent vasodilator responses to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, although this was not affected by high vitamin E treatment, vitamin E deficiency further diminished vasorelaxant response to GTN and completely abolished relaxation to ACh, with a reversal of the ACh-response so that vasoconstriction occurred. It should be mentioned that vitamin E deprivation for 4 to 12 months itself impairs endothelial relaxation, whereas smooth muscle responses are not affected (Rubino and Burnstock, 1994;Rubino et al, 1995;Ralevic et al, 1995). These investigators, however, observed only reduced vasorelaxation in vitamin E deprivation.…”
mentioning
confidence: 81%
“…Interestingly, although this was not affected by high vitamin E treatment, vitamin E deficiency further diminished vasorelaxant response to GTN and completely abolished relaxation to ACh, with a reversal of the ACh-response so that vasoconstriction occurred. It should be mentioned that vitamin E deprivation for 4 to 12 months itself impairs endothelial relaxation, whereas smooth muscle responses are not affected (Rubino and Burnstock, 1994;Rubino et al, 1995;Ralevic et al, 1995). These investigators, however, observed only reduced vasorelaxation in vitamin E deprivation.…”
mentioning
confidence: 81%